Transforming Islamic Religious Education through a Love-Based Curriculum: A Holistic Approach to Strengthening the Profile of Character-Based Students - Yahya Komarudin (EDUJAVARE: International Journal of Educational Research, 2026)
The transformation of Islamic Religious Education (IRE) is increasingly necessary to address the moral, social, and spiritual challenges faced by students in the twenty-first century. This study aims to examine the philosophical foundation, implementation, and contribution of a Love-Based Curriculum in strengthening the profile of character-based students within Islamic Religious Education. The study employed a qualitative library research design by reviewing scholarly literature, books, and international educational reports published primarily between 2020 and 2025. Data were collected through systematic literature searches and analyzed using thematic content analysis to identify recurring concepts related to holistic education, character development, Islamic educational philosophy, and compassionate pedagogy. The findings indicate that a Love-Based Curriculum integrates cognitive, emotional, spiritual, social, and moral dimensions into a unified educational framework grounded in the Islamic principles of rahmah (compassion), justice, empathy, sincerity, and respect for human dignity. Its implementation promotes caring teacher–student relationships, inclusive school cultures, reflective learning, collaborative engagement, and authentic value internalization.